Programa de Tecnologías Educativas Avanzadas: una reseña histórica / Program Of Educative Technologies Advanced: a historical review - Alonso Delgado, Julia (Actualidades Investigativas en Educación, 2007)
Reseña Histórica. El propósito de este artículo es presentar un recorrido, desde las circunstancias que llevaron a su creación, los momentos claves en su desarrollo y consolidación, así como los logros más significativos y la visión de futuro del Programa de Tecnologías Educativas Avanzadas (PROTEA) del Decanato de la Facultad de Educación de la Universidad de Costa Rica. Historical review. The purpose of this article is to present a route, from the most significant circumstances that took to their creation, the key moments in their development and consolidation, as well as profits and the vision towards the future of the Program of Educative Technologies Advanced ((PROTEA for its acronym in Spanish) of the Deanship of the Faculty of Education of the University of Costa Rica.